GAGASAN CALON PRESIDEN DAN WAKIL PRESIDEN PERSEORANGAN DALAM RANGKA PENINGKATAN KUALITAS DEMOKRASI DI INDONESIA - Siti Rodhiyah Dwi Istinah (Unissula, 2012)
The emergence of idea toward the candidates of president and vice president independently is influenced by the people distrust tendency due to the role and functioning of political parties at this time.The national leadership quality has not been measured because of many leaders tends to pragmatic and ambiguous, this is because; lack of leaders resource quality who has specific character at the branches of country power in all stratification, as well as the rising phenomenon of leader who is oriented only to maintain power. Therefore, it seems reasonable if people expect the president and vice president candidates independently appropriate to the people in the upcoming election. The efforts were made in order to be approved of presidential and vice presidential independently in the upcoming elections by recovering enactment UU No. 42 Year 2008 about the President and Vice-President Election toward UUD 1945. Additionally alternatives can be pursued in adopting an independent candidate by constitutional convention. But it seemingly sustains trouble in implementation, the constitutional practice at this time with political interests.Keywords: Candidates for President and Vice President, Independent, Democracy